The Mediating Effect of CSR Disclosure on Gender Diversity, Profitability, and Tax Avoidance - Xaviolyn Xaviolyn; Hendi Hendi; Robby Krisyadi (Jurnal Akuntansi Manado (JAIM), 2023)
This study investigates the impact of board gender diversity and profitability on tax avoidance with CSR disclosure as a mediator. The direct and indirect effects of gender diversity on board directors and profitability with tax avoidance are measured with the Structural Equation Model (SEM). In total, 216 data were analyzed from 53 companies in 2018-2022. Overall, the results show that the number of women on the board plays a vital role in the company’s information transparency. With women on the board, the level of tax avoidance decreases, and corporate CSR disclosure increases. Profitability affects the level of CSR disclosure as the disclosure of CSR will improve the image of the company and therefore increasing profitability. This research is intended to extend existing literature through the impact of the mediating effect of CSR disclosure on the relationship between board gender diversity and tax avoidance on firms listed in IDX.